Dysregulation of Biomarkers of Hemostatic Activation and Inflammatory Processes are Associated with Adverse Outcomes in Pulmonary Embolism. (January 2022) - Darwish, Iman; Fareed, Jawed; Brailovsky, Yevgeniy; Hoppensteadt, Debra; Slajus, Brett; Bontekoe, Emily; De Stefano, Frank; Reed, Trent; Darki, Amir
Introduction: The pathophysiology of pulmonary embolism (PE) represents complex, multifactorial processes involving blood cells, vascular endothelium, and the activation of inflammatory pathways. Platelet (P), endothelial (E), and leukocyte (L)-selectin molecules may play an important role in PE pathophysiology. We aimed to profile the biomarkers of inflammation, including selectins in PE patients, and compare them to healthy individuals. Materials and methods: 100 acute PE patients and 50 controls were included in this case control study. ELISA methods were used to quantify levels of selectins, inflammatory, and hemostatic biomarkers. Results: In PE patients, levels of selectin molecules as compared to controls convey increased P-selectin levels (95 ng/mL vs 40 ng/mL, p < .0001) and decreased L-selectin levels (1468 ng/mL vs 1934 ng/mL, p < .0001). Significant correlations were found between selectins and Plasminogen Activating Inhibitor-1 (PAI-1), Tumor Necrosis Factor-a (TNFa), and D-dimer. Fold change between selectins and controls is compared to other biomarkers, illustrating degrees of change comparable to TNFa, alpha-2-antiplasmin, and microparticles. L-selectin levels are inversely associated with all-cause-mortality in PE patients, (p = .040). Conclusion: These studies suggest that various thrombo-inflammatory biomarkers are elevated in PE patients. Furthermore, L-selectin levels are inversely associated with mortality outcomes.